How to educate student become competent entrepreneurs - Supardi, Endang; Islamy, Fahmi Jahidah; Muhidin, Sambas Ali; Sutarni, Nani (Jurnal Cakrawala Pendidikan, 2022)
The purpose of this study was to examine the direct or indirect effect between the entrepreneurship education variable and the student entrepreneurship competence variable in Vocational High School students. This study used a quantitative approach with the Survey Method (Explanatory Survey Method), and the test uses path analysis. The number of samples in this study found 100 students from 25 Public and Private Vocational High Schools accredited-A in the city of Bandung. The results showed that (1) entrepreneurship education had a significant effect on entrepreneurial intentions, both directly and indirectly, (2) entrepreneurship education had a significant direct effect on student entrepreneurial competencies, (3) and student entrepreneurial competencies had a significant influence on entrepreneurial intentions.  This is because the results can illustrate that entrepreneurship education in vocational high schools is good, it can be seen from the score of the entrepreneurship education variable in the high category and the form of entrepreneurship learning in vocational high schools is good. Entrepreneurship education has the highest direct influence on students' entrepreneurial competence variables. Entrepreneurship education has a significant effect on entrepreneurial intentions, but if the competence variable becomes a mediating variable, it can further increase students' entrepreneurial intentions. The results of this study are expected to be considered by vocational high schools to provide entrepreneurship education to students, so that students' competence and interest in entrepreneurship can increase.